Pediatric versus adult high grade glioma: Immunotherapeutic and genomic considerations - Aggarwal, Payal; Luo, Wen; Pehlivan, Katherine C.; Hoang, Hai; Rajappa, Prajwal; Cripe, Timothy P.; Cassady, Kevin A.; Lee, Dean A.; Cairo, Mitchell S. (Frontiers in Immunology, 2022)
High grade gliomas are aggressive malignant central nervous system tumors with a universally poor prognosis. For the first time, the most recent 2021 World Health Organization classification of central nervous system tumors has divided adult from pediatric type diffuse high grade gliomas, underscoring the biologic differences between these tumors in different age groups. Yet, historically high grade gliomas in the pediatric population have been treated similarly to adult high grade gliomas. The objective of our review is to compare high grade gliomas in the adult versus pediatric patient populations, highlighting similarities and differences in epidemiology, etiology, pathogenesis and therapeutic approaches. High grade gliomas in adults versus children have varying clinical presentations, molecular biology background, and response to chemotherapy, as well as unique molecular targets. However, increasing evidence show that they both respond to recently developed immunotherapies. This review summarizes the distinctions and commonalities between the two in disease pathogenesis and response to therapeutic interventions with a focus on immunotherapy.